Ice Melting to Release Reactants in Solution Syntheses. Issue 13 (14th February 2018) - Wei, Hehe; Huang, Kai; Zhang, Le; Ge, Binghui; Wang, Dong; Lang, Jialiang; Ma, Jingyuan; Wang, Da; Zhang, Shuai; Li, Qunyang; Zhang, Ruoyu; Hussain, Naveed; et al.
Abstract: Aqueous solution syntheses are mostly based on mixing two solutions with different reactants. It is shown that freezing one solution and melting it in another solution provides a new interesting strategy to mix chemicals and to significantly change the reaction kinetics and thermodynamics. For example, a precursor solution containing a certain concentration of AgNO3 was frozen and dropped into a reductive NaBH4 solution at about 0 °C. The ultra‐slow release of reactants was successfully achieved. An ice‐melting process can be used to synthesize atomically dispersed metals, including cobalt, nickel, copper, rhodium, ruthenium, palladium, silver, osmium, iridium, platinum, and gold, which can be easily extended to other solution syntheses (such as precipitation, hydrolysis, and displacement reactions) and provide a generalized method to redesign the interphase reaction kinetics and ion diffusion in wet chemistry. Abstract : Freezing one solution and melting it in another provides a strategy to mix chemicals and to significantly change the reaction kinetics and thermodynamics. For example, a AgNO3 solution was frozen and dropped into a reductive NaBH4 solution at about 0 °C. Atomically disperse metals can be synthesized in this fashion, and the method can be extended to other solution syntheses (precipitation, hydrolysis, and displacement reactions).